Generation Z and Digital Ecology: The Role of TikTok in Environmental Campaigning by Pandawara Group - Aminulloh, Akhirul; Qorib, Fathul; Hakim, Lukman (Jurnal Komunikasi, 2024)
Pandawara Group is a community of young environmental activists who have gained widespread attention for their waste cleanup campaigns in Indonesia. Pandawara Group utilizes the social media platform TikTok to reach a larger audience. This research aims to explore how digital technology and social media are used and influence environmental action among Generation Z. Using a qualitative approach, this research analyzes the content strategy of the TikTok social media platform. Through a qualitative approach, this research analyzes their content strategy in the context of digital ecology. The research examined eight TikTok videos with the highest number of likes on Pandawara Group's account to evaluate user engagement patterns and content elements that support campaign effectiveness. In addition, interviews were conducted with Pandawara followers at Tribhuwana Tunggadewi University to explore their perceptions of Pandawara's hygiene campaign through digital platforms. The results showed that Pandawara's authentic and visually appealing content successfully moved audiences, especially the younger generation, towards environmental activism. The study also found that their strategy of emotional storytelling and community engagement created a strong bond with their followers. In addition, the viral nature of their content significantly extended the reach of the message to a global audience. The discussion in this study highlights how such digital strategies are instrumental in creating sustainable impact for environmental advocacy. The conclusion of this study is that digital platforms are highly effective for strengthening grassroots environmental movements and suggests further research on the role of social media in ecological advocacy.